Lymphocyte transformation test in leprosy; correlation of the response with inflammation of lesions. - Bjune, G (1976)
Lymphocyte transformation tests (LTT) using 'whole washed" and 'sonicated" preparations of Mycobacterium leprae (M. leprae) as antigen were studied in eighty-one patients with borderline leprosy. The results were correlated with the histological and the clinical pictures. There was a good correlation with the histological spectrum, LTT responses generally being higher in the borderline tuberculoid leprosy patients and lower in the borderline lepromatous. However, considerable variation was noted in each group of the borderline leprosy spectrum, and it was found that this was due in part to the degree of inflammation in the skin. Thus those with 'inflamed" skin lesions had higher responses than those with 'silent" lesions, and even those with borderline lepromatous leprosy with inflamed lesions had higher responses than those with borderline tuberculoid leprosy whose lesions were silent. Those who had reversal reactions, where inflammation is very marked, had very high LTT responses which fell with treatment of the reaction with steroids. It thus appears that the LTT in leprosy is influenced by the occurrence of hypersensitivity reactions as well as by the patient's ability to resist bacillary multiplication.